Environmental science : - Cunningham, William P. (McGraw-Hill Higher Education, 2007)
This textbook focus on the environmental issues and give new pedagogical features including data analysis exercises and web-based exercises. The book consists of 25 chapters that have the same structure including case studies, Google Earth Placemarks, the latest Global data, exploring science data analysis. In addition authors give student s oppotuniies to practice critical thinking by giving the sections named "Think about it" and "What do you think. At the end of each chapters, readers can review the learning outcome and answer discussion question as well as do practice quiz.